Extracorporeal organ support and the kidney - Muciño-Bermejo, Maria-Jimena (Frontiers in Nephrology, 2022)
The concept of extracorporeal organ support (ECOS) encompasses kidney, respiratory, cardiac and hepatic support. In an era of increasing incidence and survival of patients with single or multiple organ failure, knowledge on both multiorgan crosstalk and the physiopathological consequences of extracorporeal organ support have become increasingly important. Immerse within the cross-talk of multiple organ failure (MOF), Acute kidney injury (AKI) may be a part of the clinical presentation in patients undergoing ECOS, either as a concurrent clinical issue since the very start of ECOS or as a de novo event at any point in the clinical course. At any point during the clinical course of a patient with single or multiple organ failure undergoing ECOS, renal function may improve or deteriorate, as a result of the interaction of multiple factors, including multiorgan crosstalk and physiological consequences of ECOS. Common physiopathological ways in which ECOS may influence renal function includes: 1) multiorgan crosstalk (preexisting or de-novo 2)Hemodynamic changes and 3) ECOS-associated coagulation abnormalities and 3) Also, cytokine profile switch, neurohumoral changes and toxins clearance may contribute to the expected physiological changes related to ECOS. The main objective of this review is to summarize the described mechanisms influencing the renal function during the course of ECOS, including renal replacement therapy, extracorporeal membrane oxygenation/carbon dioxide removal and albumin dialysis.